The effects of alfentanil on emergence agitation in children under general anesthesia: a meta-analysis of randomized controlled trials - Xu, Yuanling; Ding, Kun; Zhao, Xuemei; Sun, Yingying (Frontiers in Pediatrics, 2025)
BackgroundEmergence agitation (EA) is characterized by excessive reactivity and sensory impairment that occurs in children after general anesthesia. Alfentanil is a µ-opioid receptor with rapid onset and short duration, widely used in minor surgery. The aim of this meta-analysis is to assess the effect of alfentanil on the incidence of EA in children undergoing general anesthesia.MethodsPubMed, Cochrane Library, Embase, and Web of Science databases were reviewed to search for related trials published before April 30, 2025. The primary outcome was the incidence of EA. Secondary outcomes included rescue analgesia, postoperative nausea and vomiting (PONV), emergence time, extubation time, and time to discharge from post-anesthesia care unit (PACU).ResultsThe study extracted from 5 studies including 532 patients. Compared to saline, alfentanil reduced the incidence of EA in children (RR = 0.54; 95% CI: 0.42–0.70; P < 0.01). In addition, alfentanil decreased the use of rescue analgesic (RR = 0.5; 95% CI: 0.38–0.65; P < 0.01), did not increase the incidence of PONV (RR = 1.39; 95% CI: 0.67–2.88; P = 0.37). According to the GRADE system, the quality of evidence was moderate for the incidence of EA.ConclusionsLimited available evidence suggests that alfentanil is associated with a lower incidence of EA in children. However, further high-quality studies are needed to verify the effect of alfentanil in preventing the occurrence of EA in children undergoing general anesthesia.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023448260, PROSPERO CRD42023448260.